Co-occurrence of Anti-N-Methyl-D-Aspartate Receptor Encephalitis and Anti-myelin Oligodendrocyte Glycoprotein Inflammatory Demyelinating Diseases: A Clinical Phenomenon to Be Taken Seriously - Ren, Yijun; Chen, Xiqian; He, Qiang; Wang, Renchun; Lu, Wei (Frontiers in Neurology, 2019)
Background: Anti-N-methyl-D-aspartate receptor (NMDAR) immunoglobulin G antibodies which exist on myelin sheaths, composed of oligodendrocytes, especially target GluN1 subunits and are highly characteristic of anti-NMDAR encephalitis which is a newly recognized autoimmune encephalitis (AE) characterized by psychiatric symptoms, behavioral abnormalities, seizures, cognitive impairment and other clinical symptoms. Myelin oligodendrocyte glycoprotein (MOG) is a type of protein which is expressed on the surface of oligodendrocytes and myelin in the central nervous system. Anti-MOG antibodies cause demyelination. In some rare reported cases, these two types of antibodies have been found to co-exist, but the underlying mechanisms remain unknown. Case presentation: Here we report cases of 4 inpatients (median age 31.5 years, age range 27–43 years) from The Second Xiangya Hospital of Central South University between March 2018 and April 2019. Two of the cases were first diagnosed as anti-NMDAR encephalitis and had developed visual impairments in the course of the dosage reduction during corticosteroid therapy. They were found at the time, to have anti-MOG antibody-positive CSF and/or serum. Another patient was diagnosed with anti-MOG inflammatory demyelinating diseases (IDDs) when he tested double positive for both anti-NMDAR and anti-MOG antibodies early in the course of his illness. Over the course of the dosage reduction during corticosteroid therapy, his symptoms deteriorated; however, anti-MOG antibody levels elevated while anti-NDMAR antibody levels remained low. The other patient had initially developed psychiatric symptoms and limb weakness. She was also double positive for anti-NMDAR and anti-MOG antibodies early in the course of her illness. However, over the course of the dosage reduction during corticosteroid therapy, her symptoms worsened and levels of both antibodies elevated. Conclusion: Anti-NMDAR and anti-MOG antibodies may coexist in rare cases. In addition, anti-NMDAR encephalitis and anti-MOG inflammatory demyelinating diseases may occur either simultaneously or in succession. Thus, when a patient is diagnosed with either of these two diseases, but exhibits symptoms of the other disease, the possibility of co-occurrence with both these diseases should be considered and the appropriate antibodies should be accurately detected to enable prompt selection of appropriate treatments by the physicians.